Relationship Between Crude Oil Price Fluctuations, Economic Growth, Inflation, and Exchange Rate in Indonesia 1967-2019 - Salwinar Aprin Nitami; Banatul Hayati (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Economic fluctuations can be caused by demand shocks and supply shocks. One of the supply shocks is caused by changes in world crude oil prices. As a net importer of crude oil, any change in crude oil prices makes domestic economic activity vulnerable to these shocks. The purpose of this study is to determine the effect of fluctuations in world crude oil prices on economic variables in Indonesia in the form of economic growth, inflation, and exchange rates. In addition, this study also analyzes the causal relationship between these variables. The type of data used is secondary data sourced from the BP Statistical Review of World Energy and the Worldbank. This research uses the VAR/VECM method, the research period was carried out during the years 1967-2019. The results showed that during 1967-2019 fluctuations in world crude oil prices had a significant positive effect on economic growth and had a significant negative effect on inflation and the exchange rate in the long run. Meanwhile, in the short term, world crude oil price fluctuations do not significantly affect economic growth, inflation, and the exchange rate. The results of the Granger causality show that there is no two-way causality relationship between variables.Keywords: Fluctuation World Crude Oil Price, Economic Growth, Inflation, Exchange Rate, VAR/VECM, Granger Causality Test